UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM PENERAPAN KARAKTER TOLERANSI SISWA DI SMA NEGERI 2 MALANG - Ummi Faiqotul Karimah; Qurroti A'yun; Imam Safii (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
At the time of the Prophet Muhammad, character education was really used. This is evidenced by the command of Allah SWT that the first and most important mission of the Prophet Muhammad was to perfect the morals of all his people. The discussion of the substance of the meaning of personality is the same as the concept of morality and Islam. Both discuss human behavior. Therefore, applying personality education to students in order to understand human behavior related to Allah SWT, oneself, fellow humans, the environment and nationality as well as reflected in thoughts, attitudes, emotions, words and behavior. The location of this research is in SMA Negeri 2 Malang. This study uses a qualitative method where data collection uses the method of observation, interviews and documentation and is supported by the opinions of experts. The efforts of Islamic Religious Education Teachers in forming the tolerance character of students at SMA Negeri 2 Malang have been good, carried out through habituation methods inside and outside the classroom, such as getting used to praying together before and after learning with their religious beliefs, and PAI teachers conveying material about the importance of the character of tolerance towards students through the lecture method in the form of advice about the importance of the character of tolerance in capable classes outside the classroom, with teachings from Islamic religious education teachers so that this school develops tolerance for students of different religions.